Qualidade na televisão - Medeiros, Sônia Maria Guedes de (2008)
The general objective of Quality in Television , a research based on the problematization of the ways whereby the media builds values, is to examine the television broadcasting flow throughout a week. A semiotic map is used to identify and position the cultural products which, in their diversity, are semiotized and circulated with consumption values connected to specific communication contracts. The specific objectives are structured around four points: reading of the seven concepts of quality in television by Mulgan; classification, by genre, of the programming flow of seven broadcasting companies Bandeirantes, Cultura, Gazeta, Globo, Record, Rede TV! and SBT from February 7 to 12, 2006; positioning of the programs on semiotic maps; and examination of the seven semiotic maps of consumption values with respect to the seven concepts of quality, indicating diversity in programming. The research is based on semiotics as the theoretical-methodological basis, on television theory and on critical theory. The thesis consists of four parts, according to the aforementioned specific objectives. The first chapter, Searching for Quality , is based on Geoff Mulgan and Arlindo Machado. The second chapter, Televisual Flow , is based on Raymond Williams. The third, Construction and circulation of consumption values , taken from the structure of Jean-Marie Floch and Andrea Semprini s semiotic map, is used as a tool to examine the televisual flow. The conclusion, discusses the results of an analysis of aspects of quality considered by Mulgan and of values of consumption in the televisual flow, here, the author argues that quality in television is not merely a concept, nor is it translated into technical results or technological innovations. From a broader standpoint, it implies a complex social process, starting from the production of a professional team to its interpretation by the spectator. The latter, seeking to shake off his passiveness in a dynamic process, a spiraling movement of the audience, not only attempts to denounce faults and squalidness but also to promote the context of reception and understand the diversity of television media in the contemporary context of capitalism. The authors that contribute to this discussion include Jean Baudrillard, Muniz Sodré, Krishan Kumar and Anthony Giddens